Transcervical uterine flushing and embryo transfer in sheep: Morphophysiological basis for approaches currently used, major challenges, potential improvements, and new directions (alas, including some old ideas) - Gonçalves, Joedson Dantas [UNESP]; Dias, Jenniffer Hauschildt; Machado-Neves, Mariana; Vergani, Gabriel Brun [UNESP]; Ahmadi, Bahareh; Pereira Batista, Ribrio Ivan Tavares; Souza-Fabjan, Joanna Maria Gonçalves; Oliveira, Maria Emilia Franco [UNESP]; Bartlewski, Pawel Mieczyslaw; da Fonseca, Jeferson Ferreira (Elsevier, 2024)
At present, the success of non-surgical embryo recovery (NSER) and transfer (NSET) hinges upon the cervical passage of catheters, but penetration of the uterine cervix in ewes is problematic due to its anatomical structure (i.e., long and narrow cervical lumen with misaligned folds and rings). It is a major obstacle limiting the widespread application of NSER and NSET in sheep. While initial attempts to traverse the uterine cervix focused on adapting or re-designing insemination catheters, more recent studies demonstrated that cervical relaxation protocols were instrumental for transcervical penetration in the ewe. An application of such protocols more than tripled cervical penetration rates (currently at 90–95 %) in sheep of different breeds (e.g., Dorper, Lacaune, Santa Inês, crossbred, and indigenous Brazilian breeds) and ages/parity. There is now sufficient evidence to suggest that even repeatedly performed cervical passages do not adversely affect overall health and reproductive function of ewes. Despite these improvements, appropriate selection of donors and recipients remains one of the most important requirements for maintaining high success rates of NSER and NSET, respectively. Non-surgical ovine embryo recovery has gradually become a commercially viable method as even though the procedure still cannot be performed by untrained individuals, it is inexpensive, yields satisfactory results, and complies with current public expectations of animal welfare standards. This article reviews critical morphophysiological aspects of transcervical embryo flushing and transfer, and the prospect of both techniques to replace surgical methods for multiple ovulation and embryo transfer (MOET) programs in sheep. We have also discussed some potential pharmacological and technical developments in the field of non-invasive embryo recovery and deposition.
Keywords: Assisted reproductive technologies; Biomedical engineering, microrobotics; Cervical dilation; Sheep; Transcervical passage